The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1001/archpedi.158.10.988
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Behavior in an Urban US Sample of School-aged Children

Abstract: A sizeable proportion of elementary schoolchildren sleep less than the recommended 9 hours. Across the age range, decreases in sleep time and, in ethnic minorities, increasingly delayed bedtimes suggest emerging sleep restriction in preadolescents. Observed ethnic differences in sleep behavior highlight the need for better understanding of the social and environmental influences encouraging these sleep patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
125
4
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(147 citation statements)
references
References 32 publications
13
125
4
2
Order By: Relevance
“…With regard to socio-demographic factors, children of Caucasian ethnicity have been indicated to sleep longer than children of other ethnicities. [6][7][8][9] Age is inversely associated with sleep deprivation. 10 The role of environmental factors on sleep duration is unclear, but there are indications that the physical and socio-cultural home environment play an important role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to socio-demographic factors, children of Caucasian ethnicity have been indicated to sleep longer than children of other ethnicities. [6][7][8][9] Age is inversely associated with sleep deprivation. 10 The role of environmental factors on sleep duration is unclear, but there are indications that the physical and socio-cultural home environment play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to socio-demographic factors, children of Caucasian ethnicity have been indicated to sleep longer than children of other ethnicities. [6][7][8][9] Age is inversely associated with sleep deprivation. 10…”
mentioning
confidence: 99%
“…[1][2][3][4] Community and multi-site studies have consistently reported that up to 20% to 25% of US children and adolescents experience a range of sleep problems. [5][6][7][8][9][10] Inadequate sleep takes many forms: difficulty with sleep onset, length, or circadian rhythms with resulting daytime sleepiness experienced by otherwise healthy children; disturbed sleep associated with acute and chronic illness; and primary sleep disorders. The least attention has been paid to the first group, and there is little consensus about the second.…”
mentioning
confidence: 99%
“…These findings contribute to the growing body of literature demonstrating a negative association between sleep duration and BMI among children [33][34][35][36][37][38]. While underlying physiological mechanisms are not well understood, clinical evidence suggests hormonal and neural regulation may be altered from inadequate sleep [4,39,40].…”
Section: Discussionmentioning
confidence: 63%
“…Metabolic health consequences of restricted or inadequate sleep are well documented in adults [39,40], and are potentially more concerning in developing children as the impacts can be lifelong. The impacts of short sleep duration extend beyond metabolic health and have been directly correlated to performance on neurocognitive function [33,36] (Table 3). This study expands on the currently limited body of literature of sleep patterns in Latino communities, particularly of Mexican heritage.…”
Section: Discussionmentioning
confidence: 99%